Quality of water for human consumption in the balsa communities in the middle, Julián and Severino of the Carrizal micro-basin, Ecuador - Lucas Vidal, Leonel Rolando (2018)
A study on the quality of water for human consumption was carried out in Julián, Severino and Balsa en Medio communities located in the micro-basin of the Carrizal River in the province of Manabí, Ecuador. Surface water samples were taken to determine chemical, physical and microbiological properties. To establish the quality of the water in the sampling sites, the ICA NSF water quality index was used, which allows weighing parameters assigning a weight. A completely randomized design with three repetitions was used, taking the localities as treatments. The analysis of variance was carried out through the InfoStat program and the average comparisons through the Tukey test at 5% probability. The physical chemical variables of the locality of Severino showed values that induced lower water quality than those obtained for the localities of Julián and Balsa en Medio, with a similar behavior among themselves. From the microbiological point of view, the highest health risks correspond to the locality of Balsa en Medio, followed by Severino; while the lowest risk corresponded to the town of Julián. According to the ICA NSF criteria, the waters of Balsa en Medio and Julián are classified as “poorly polluted waters”, while the waters of the community of Severino are classified as “contaminated waters”.